Clinical characteristics of non‐radiographic axial spondyloarthritis: Results of the Korean Nonradiographic Axial SPondyloArthritis (KONASPA) data. (11th July 2021) - Jeong, Hyemin; Kim, Yong‐Gil; Kim, Tae‐Hwan; Kim, Tae‐Jong; Park, Min‐Chan; Seo, Mi Ryoung; Shin, Kichul; Oh, Ji Seon; Lee, Sang‐Hoon; Lee, Yeon‐Ah; Lee, Eun Young; Baek, Han Joo; et al.
Abstract: Aim: To evaluate clinical characteristics and natural history of non‐radiographic axial spondyloarthritis (nr‐axSpA) using KOrean Nonradiographic Axial SPondyloArthritis (KONASPA) data. Methods: Data were collected from 11 centers in South Korea. A total of 278 patients with nr‐axSpA from January 2018 to July 2020 were included. Demographic data, clinical features, comorbidities, disease activity, medications, and laboratory results were collected. Results: Mean age at symptom onset was 28.2 ± 14.2 years. Of 278 patients, 152 (54.7%) were male. Mean Bath Ankylosing Spondylitis Disease Activity Index at diagnosis was 3.5 ± 2.1. Dyslipidemia was the most common comorbidity (8.4%), followed by hypertension (6.1%). Mean age at diagnosis of nr‐axSpA was older in female patients than in male patients (31.8 ± 15.8 years vs 24.9 ± 12.0 years, P  < 0.001). Enthesitis and uveitis were more frequently found in female patients than in male patients. Thirty‐one (11.1%) participants with nr‐axSpA progressed to ankylosing spondylitis. The median follow‐up duration was 48 months. In multivariable Cox regression analysis, age at symptom onset (hazard ratio [HR] 0.93, 95% confidence interval (CI) 0.88‐0.97, P  = 0.006), body mass index (BMI) (HR 1.24, 95% CI 1.06‐1.44, P  = 0.005) and sacroiliitis grade (HR 1.86, 95% CI 1.19‐2.92, P  = 0.006) were associated with progression to ankylosing spondylitis. Conclusions: Results of nationwide data revealed that women with nr‐axSpA showed a late disease onset and more extra‐articular manifestations than men. Young age at symptom onset, high BMI, and presence of radiographic sacroiliitis at diagnosis were risk factors for progression to AS.